How rice can contribute to solving the climate crisis - Sander, Björn Ole (International Rice Research Institute, 2022)
Presented during the conference of the National Agriculture and Food Research Organization of Japan on October 2022, the presentation tackled the rice–food security–climate change nexus and the IRRI Climate Change Mitigation Strategy.